Effect Of Pinealectomy And Melatonin Effect On Gonadal Development Of Catfish (Heteropneustes Fossilis) During Postspawning Period - Rani, Sudesh (Zenodo, 2018)
Pinealectomy (Px) and Melatonin treatment effect was examined in the male and female catfish Heteropneustes fossilis for 60 days. This experiment was done in post spawning period of the reproductive phase of catfish. The results of this study revealed that pinealectomy (Px) causes inhibitory effects on the GSI and the histology of the male catfish, while in the female catfish stimulatory effects on both was observed. In histological study of the female catfish stage I oocytes were present in the ovary of the control group whereas catfish administered with low (25, 50 mg) and high doses (100, 200, 400 mg) of melatonin very less number of stage I oocytes were seen but the percentage of atretic oocytes were increased when the melatonin doses were increased. The present study showed that the melatonin dose causes follicular atresia in female catfish during the post spawning period. Histological studies of male catfish showed large number of remnants of spermatozoa (rsz) in the testes of the control group while very little elevation of rsz were seen in the somniferous lobules with the increased in the melatonin dose. The result suggested that the effect of pinealectomy and melatonin treatment is mediated through an action of hypothalamo-hypophyseal gonadal axis. In conclusion, the melatonin played an important role to control the gonadal maturation in the catfish H. fossilis during the post spawning period. : {"references": ["Alvarino, J., Rebollar, P., Olmedo, M., Alvarez Blazquez, B., Ubilla, E., & Peleteiro, J. (2001). Effects of melatonin implants on reproduction and growth of turbot broodstock. Aquaculture International, 9(6), 477-487", "Aripin, S.A., Jintasataporn, O., & Yoonpundh, R. (2015). Effects of exogenous melatonin in Clarias macrocephalus male broodstock first puberty stage. Journal of Aquaculture Research and Development, 6(2), 1.", "Bhattacharya, S., Chattoraj, A., & Maitra, S.K. (2007). Melatonin in the regulation of annual testicular events in carp Catla catla: evidence from the studies on the effects of exogenous melatonin, continuous light, and continuous darkness. Chronobiology International, 24(4), 629-650.", "Bhattacharyya, S., Dey, R., & Maitra, S. (2005). Photoperiodic regulation of annual testicular events in the Indian major carp Catla catla. Acta Zoologica, 86(2), 71-79.", "Chattoraj, A., Bhattacharyya, S., Basu, D., Bhattacharya, S., Bhattacharya, S., & Maitra, S. K. (2005). Melatonin accelerates maturation inducing hormone (MIH): induced oocyte maturation in carps. General and Comparative Endocrinology, 140(3), 145-155.", "Collin, J.P., Voisin, P., Falcon, J., Faure, J.P., Brisson, P., & Defaye, J.R. (1989). Pineal transducers in the course of evolution: molecular organization, rhythmic metabolic activity and role. Archives of Histology and Cytology, 52(Supplement), 441-449.", "De Pedro, N., Martinez Alvarez, R.M., & Delgado, M.J. (2008). Melatonin reduces body weight in goldfish (Carassius auratus): effects on metabolic resources and some feeding regulators. Journal of Pineal Research, 45(1), 32-39.", "de Vlaming, V.L., Wiley, H. S., Delahunty, G., & Wallace, R.A. (1980). Goldfish (Carassius auratus) vitellogenin: induction, isolation, properties and relationship to yolk proteins. Comparative Biochemistry and Physiology Part B: Comparative Biochemistry, 67(4), 613-623", "Dziewulska, K., & Domagala, J. (2003). Histology of salmonid testes during maturation. Reproduction Biology, 3(1), 47-61.", "Francis, T., Ramanathan, N., & Padmavathy, P. (2004). Role of the pineal organ and melatonin in fish. World Aquaculture. 69, 21-23.", "Garcia Allegue, R., Madrid, J., & Sanchez Vazquez, F. (2001). Melatonin rhythms in European sea bass plasma and eye: influence of seasonal photoperiod and water temperature. Journal of Pineal Research, 31(1), 68-75.", "Garg, S. (1987). Seasonal effects of pinealectomy on testicular recrudescence and secretory activity of seminal vesicles in the catfish Heteropneustes fossilis (Bloch). Journal of Fish Biology, 30(4), 377-387.", "Garg, S. (1989). Effect of pinealectomy, eye enucleation, and melatonin treatment on ovarian activity and vitellogenin levels in the catfish exposed to short photoperiod or long photoperiod. Journal of Pineal Research, 7(2), 91-104.", "Iigo, M., & Aida, K. (1995). Effects of season, temperature, and photoperiod on plasma melatonin rhythms in the goldfish, Carassius auratus. Journal of Pineal Research, 18(2), 62-68", "Lopez Olmeda, J., Madrid, J., & S\u00e1nchez Vazquez, F. (2006). Melatonin effects on food intake and activity rhythms in two fish species with different activity patterns: diurnal (goldfish) and nocturnal (tench). Comparative Biochemistry and Physiology Part A: Molecular and Integrative Physiology, 144(2), 180- 187.", "Mokae, L., Smit, N., & Wagenaar, G. (2013). Comparative histomorphological assessment of the testes of two Clarias species from the Okavango Delta Panhandle, Botswana. Tissue and Cell, 45(1), 7-20.", "Nath, P. (2005). Seasonal effects of melatonin on ovary and plasma gonadotropin and vitellogenin levels in intact and pinealectomized catfish, Clarias batrachus (Linn). Indian Journal of Experimental Biology.43,224-232.", "Nayak, P., & Singh, T. (1988). Effect of Pinealectomy on Testosterone, Estradiol\u201017\u03b2, Esterone, and 17\u03b1\u2010Hydroxyprogesterone Levels During the Annual Reproductive Cycle in the Freshwater Catfish, Clarias batrachus. Journal of Pineal Research, 5(5), 419-426.", "Nayak, P., Yadav, A., & Singh, T. (1987). Effects of pinealectomy on some sex steroid profiles during annual reproductive cycle in Clarias batrachus. Asia and Oceania Society of Comperative Endocrinology,3(4), 284-285.", "Pinillos, M., De Pedro, N., Alonso Gomez, A., Alonso Bedate, M., & Delgado, M. (2001). Food intake inhibition by melatonin in goldfish (Carassius auratus). Physiology and Behavior, 72(5), 629-634.", "Rani, S., & Sabhlok, V. (2014). Effect of pinealectomy on plasma na k and ca in catfish Clarias batrachus under different salinity levels. Indian Journal of Experimental Biology,43(3),224-232.", "Renuka, K., & Joshi, B. (2010). Melatonini nduced changes in ovarian function in the freshwater fish Channa punctatus (Bloch) held in long days and continuous light. General and Comparative Endocrinology, 165(1), 42-46.", "Rubio, V., Sanchez Vazquez, F., & Madrid, J. (2004). Oral administration of melatonin reduces food intake and modifies macronutrient selection in European sea bass (Dicentrarchus labrax, L.). Journal of Pineal Research, 37(1), 42-47.", "Shimizu, A. (2003). Effect of photoperiod and temperature on gonadal activity and plasma steroid levels in a reared strain of the mummichog (Fundulus heteroclitus) during different phases of its annual reproductive cycle. General and Comparative Endocrinology, 131(3), 310-324.", "Singh, N., Aggarwal, N., & Singh, H. (1994). In Advances in Fish Biology and Fisheries: Hindustan Publishing Corporation, New Delhi. Acta Hydrobiologica, 1 (36), 3-15.", "Singh, R., Singh, A., & Tripathi, M. (2012). Melatonin induced changes in specific growth rate, gonadal maturity, lipid and protein production in Nile tilapia and Oreochromis niloticus (Linnaeus 1758). Asian Australasian Journal of Animal Sciences, 25(1), 37.", "Sundararaj, B. (1981). Reproductive physiology of teleost fishes. A review of present knowledge and needs for future research. Aquaculture development and coordination programme, Rome. Project report- Adcp/Rep/81. 16, 88-103.", "Sundararaj, B.I., & Keshavanath, P. (1976). Effects of melatonin and prolactin treatment on the hypophysialovarian system in the catfish, Heteropneustes fossilis (Bloch). General and Comparative Endocrinology, 29(1), 84-96.", "Sundararaj, B.I., & Vasal, S. (1976). Photoperiod and temperature control in the regulation of reproduction in the female catfish Heteropneustes fossilis. Journal of the Fisheries Board of Canada, 33(4), 959-973.", "Taylor, J., Migaud, H., Porter, M., & Bromage, N. (2005). Photoperiod influences growth rate and plasma insulin like growth factor I levels in juvenile rainbow trout, Oncorhynchus mykiss. General and Comparative Endocrinology, 142(1-2), 169-185."]}